Intercountry Adoption in Indonesia - Allagan, Tiurma M. P. (UI Scholars Hub, 2018)
Indonesia regulates the Intercountry Adoption in its national law and regulation. Besides the Intercountry Adoption, it also regulates the adoptions which have foreign elements, yet excluded from the Intercountry Adoption pursuant to the national law. This writing shall What the requirements are and how the process is of those adoptions are the main topic of this writing, as well as the appliance of Principle of Nationality in those regulations. The research method of this writing is normative research to the prevailing rules and regulations includes the Indonesian district courts decisions which randomly taken. The result of this writing to opine the harmony or give advice, if any, upon the regulations of the intercountry adoptions and adoptions which contain foreign elements towards the Bill of Indonesian Private International Law.